1975
DOI: 10.1002/jpln.19751380608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphate dissolving bacteria and phosphate fertilization on the P‐uptake by pea plants cultivated in a calcareous soil

Abstract: Einfluß von phosphatlösenden Bakterien und Phosphatdüngung auf die Phosphataufnahme von Erbsenpflanzen auf Kalkböden. In Gefäßversuchen im Gewächshaus wurde in Gegenwart und Abwesenheit von phosphatlösenden Bakterien (PDB) der Einfluß von Superphosphat und Thomasphosphat auf die Phosphataufnahme von Erbsenpflanzen aus einem Kalkboden untersucht. Durch Beimpfung mit PDB und/oder durch die Phosphatdüngung wurde die Phosphataufnahme der Erbsenpflanzen erhöht. Alleinige Anwendung von PDB, Superphosphat oder Thomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
(1 reference statement)
3
5
0
Order By: Relevance
“…In the case of inoculation and fertilization with one half of the usual rate, P-uptake and dry weight were more than one and a half of the control. A number of other previous research findings confirm the results presented in this paper (Mishustin et al 1972 andKabesh et al 1975). The general conclusion from the behaviour of phosphate dissolving bacteria is that, despite enrichment of the soil with this type of microorganism, more than one inoculation might be advantageous.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…In the case of inoculation and fertilization with one half of the usual rate, P-uptake and dry weight were more than one and a half of the control. A number of other previous research findings confirm the results presented in this paper (Mishustin et al 1972 andKabesh et al 1975). The general conclusion from the behaviour of phosphate dissolving bacteria is that, despite enrichment of the soil with this type of microorganism, more than one inoculation might be advantageous.…”
supporting
confidence: 92%
“…One approach to increasing the efficiency of phosphate fertilizers for crop growth in calcareous soils has been to inoculate such soils with phosphate dissolving bacteria (e. g. Kabesh et al 1975 andSuberet al 1977). Responses to this treatment, however, have been very different as observed by Ralston and McBride 1976 who reported a range of responses in terms of yield and P-uptake by legume plants from feeble to significant increases.…”
Section: Introductionmentioning
confidence: 99%
“…phosphaticum has been used as microbial fertilizer (Phosphobactrin) and applied to millions of hectares in Europe and the Soviet Union (Cooper, 1959) to increase P availability to a variety of crops. Moreover, several investigators have reported increases in yields of different crops 181 as a result of Phosphobacterin application to calcareous soils (Kabesh et al, 1975;Osman et al, 1974;Saber et al, 1975). More attention has apparently given to the role of phosphate-dissolving bacteria (PDB) than that of phosphate dissolving fungi (Agnihorti, 1970;Barthakur, 1978).…”
Section: Introductionmentioning
confidence: 96%
“…Since then there have been various reports on counting and selection of, and plant inoculation with phosphate-solubilizing bacteria (Bajpai and Sundara Rao, 1972;Banik and Dey, 1981;E1 Gibaly et al, 1977;Kabesh et al, 1975;Leyval and Berthelin, 1983;Louw and Webley, 1958;Raghu and MacRae, 1966;Ralson and McBride, 1976;Sperber, 1958;Swaby and Sperber, 1958). Varied effects of such inoculations have been observed in term of presence of available P in the soil (Azcon et al, 1976), plant growth and P nutri-11 tion.…”
Section: Introductionmentioning
confidence: 96%